Tennessee Extension Broadcasting: Developing a Public Information Tool During Radio's Golden Years - Ned Browning (Journal of Applied Communications, 1985)
Public information sits in a delicate balance. On Ihe one hand, in a free and open democracy, the government must inform people of its activities. On Ihe other, any information activities of its agencies are open to charges of partisan propaganda.